Mechanical characteristics of poly (ethylene vinyl acetate) foams with graphene for the applications in sport footwear - Andrey V. Lunchev; Aleksandr Kashcheev; Alfred ling Yoong Tok; Vitali Lipik (Polymer Testing, 2022)
The study of laboratory samples of poly(ethylene vinyl acetate) (EVA) foams were followed by the manufacturing of real running shoes with outsole composition based on optimization data obtained from laboratory research. Samples EVA foams with 0.1, 0.2, 0.5, and 1.0 wt% (0.1, 0.2, 0.6 and 1.1 phr respectively) of graphene and different amounts of cross-linking agent were made. After the analysis of mechanical properties of laboratory samples, the concentrations of 0.1 and 0.2 phr of graphene were chosen to make industrial prototypes of actual running shoes. Industrial samples of footwear with EVA outsole containing graphene possess interesting combination of properties. The prototypes of footwear with graphene demonstrate the increase of stiffness on the axial axis, which is 30% higher than for reference footwear, which is a very useful property for propulsion during running. At the same time, the samples with graphene are twice softer based on compression test, that means cushioning property is better. In addition, the prototype with 0.2 phr of graphene shows superior abrasion properties – 40% higher compared to the reference samples. It will help to keep esthetical properties and lifespan of shoes with graphene longer than common ones.